Analyzing Physiologic occlusion - M. Emamie (Tehran University of Medical Sciences, 1987)
Generally speaking, when preserving and restoring the gnathostomatic system the dentist controls tooth morphology to insure proper distribution of stress. So, we restore a portion of a tooth or all the teeth in such a manner as to subject the associated parts of the system to the least stress. We evaluate our diagnosis and control it in our treatment. The treatment should be based on the scientific method. We create optimal occlusion or a desirable functional state of the masticatory system.  Many persons with occlusal imperfections will not have symptoms of functional disorders. This is the psychological adaptive capacity of the neuromuscular system, teeth, dental arches, and periodontal tissues.Recent developments in dental material, technology and instruments however, have simplified the taskaf restoring rebuilding and rehabilitating diseased mouths. So, optimum oral health and function should be the prime objective of all treatment procedures. Because the ultimate aim will always be to restore the mouth to health and preserve this status throughout the life of a patient.